Federal Court Cases: Integrated Data Base Bankruptcy Petitions, 1999 ([Verlag nicht ermittelbar], 2004)
The purpose of this data collection is to provide an official public record of the business of the federal bankruptcy courts. The data includes all petitions filed under the Bankruptcy Code in the U.S. Bankruptcy Courts on or after October 1, 1993, and any petitions filed before October 1, 1993, that were still pending on that date. The records are organized according to the fiscal year of termination with cases still pending at the end included in a separate pending data set. For the bankruptcy data, the unit of analysis is a single case.